Barragens de rejeitos de mineração no Brasil: principais tipos de barragens, instrumentação e monitoramento - MARTINS, Luís Fernando (2019)
Brazil is a country with continental dimensions and great diversity of subsoil, providing large mineral reserves of niobium, nickel, manganese, aluminum, iron and others, that makes it very attractive to mining. With the expansion of mineral commodities in the 2000s and the increased demands for minerals, because of world population growth and consumption, mining intensified. Thereby, the volume of tailings being generated increased dramatically and larger areas for the disposal was necessary. Usually, this disposal is made in containment dams, whose volume is increased by heightening. In Brazil, the upstream method is the mostly used by mining companies, mainly for its low cost and simplicity of execution. The present study verified that currently has 662 tailings dams in Brazil DNPM and the most of them are Minas Gerais (almost 48%), fallow by São Paulo (11%) and Pará (10%). Furthermore, was observed that iron ore tailing is the main content in this dams. 78% of Brazilian dams have until height 30 meters and approximately 80% have a low risk of failure. In relation to tailing dams failures, which may affected communities and environment and causes deaths, this work observed that the principal causes of failure was associated to unusual weather events. Was also observed that the most of these accidents can be avoided by available technologies and the monitoring and instrumentation of dams are a way to minimize these accidents. For this, it is necessary a good operation of the instrumentation with the elaboration of an instrumentation plan, correct selection of the instruments, verification of its precision and its reliability, as well as the precise analysis of the data provided by the instrumentation.